Neuronale Korrelate des Psychoserisikosyndroms: Strukturelles Neuroimaging bei Personen mit erhöhtem Psychoserisiko = Structural neuroimaging markers in individuals with ultra-high risk conditions for developing psychosis - Hirjak, Dusan; Thomann, Philipp; Depping, Malte S.; Wolf, Robert Christian (Nervenheilkunde, 2013)
Request PDF | Structural Neuroimaging Markers in Individuals with ultra-high Risk Conditions for developing Psychosis | At present, ultra-high risk (UHR) conditions for developing psychosis are clinically defined syndromes. Early recognition of UHR individuals... | Find, read and cite all the research you need on ResearchGate